Subsidios, vivienda digna y hábitat: percepciones de los residentes, beneficiarios de subsidios habitacionales, sobre la materialización del derecho a la vivienda digna en el Macroproyecto de Interés Social Nacional Ciudad Verde, Soacha, Colombia, (2009-2015) - Caicedo Medina, Julián Alberto (2022)
The perception of the residents, attended through subsidies in the housing policy, on the attributes of the right to decent housing are an indicator of their inhabiting situation, recognizing the latter the particularities that are determined by the life trajectory, socio- economic status, experiences in their dwellings inhabiting, values and cultural traditions, amongst others; and a mechanism for the assessment of the Project and the housing policy when analyzing the conditions of the materialization of the attributes of the right to decent housing in the case of the Macroprojecto de Interés Social Nacional (MISN) Ciudad Verde, in the municipality of Soacha, department of Cundinamarca, Colombia. This characterization of the living or inhabiting situation of the residents allows us to establish the differences that appear between groups of residents who are beneficiaries of family housing subsidies -SFV- and the ones who are beneficiaries of in-kind family housing subsidies -SFVE- with dissimilar accommodations origins in an urban housing megaproject, with similar socio-spatial conditions, in terms to the characteristics and urban services that are offered by the urban enviroment to their dwellings. \nIn this research, the proposed methodological approach considers the resident population in the MISN Ciudad Verde as a unit of observation and adopting as a unit of analysis the attributes of the right to decent housing from the perceptions of residents, resulting from the understanding, adaptation, and appropriation of the situation of inhabiting from the interpretation of the attributes of the right to decent housing in reference to the right to the city. The perceptions of residents who are beneficiaries of family subsidies differ and express the particularities of the living situation referred to the components and attributes of the right to decent housing. Among the determinants that define the perception of the living situation are the housing trajectory, daily housing experience, gender, age, as well as their sociocultural and economic status. The differences between the interviewed groups present greater differences in the private sphere (building and economic components) and present greater coincidences in the public sphere (urban environment and socio-cultural component).